Successful Resection of Lymphangioma of the Neck and Mediastinum Presenting as Stridor in a 12 Year Old Child (Cardiovascular Journal, 2017)
Lymphangiomas are congenital malformations of lymphatic tissue. This benign condition is generally found in the neck region and is discovered by 2 years of age. Here we report the case of a 12 year old child who presented with a cervical and mediastinal cystic hygroma that had progressed to such a space occupying nature as to cause the shifting of the trachea. The entire mass was successfully resected with a lower neck incision. Our case suggests the necessity of considering cystic lymphangioma in the differential diagnosis of lateral neck masses and use of adequate imaging to substantiate the preoperative diagnosis.Cardiovasc. j. 2017; 9(2): 167-169